The Influence of Artificial Intelligence Usage of ChatGPT and Work Motivation on Teaching Readiness of Educators in Leuwiliang Bogor - Sari Febrianti; Alifia Taufika Rahma; Dhioatmaja Megafajari; Vera Maya Santi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
The rapid integration of artificial intelligence, particularly ChatGPT, has reshaped instructional practices and teacher preparation, while raising questions about educators’ readiness to adapt effectively. This study examines the influence of ChatGPT usage and work motivation on the teaching readiness of educators in Madrasah Tsanawiyah in Leuwiliang, Bogor. Employing a quantitative approach, data were collected from 155 teachers using validated questionnaires and analyzed through multiple linear regression. The findings reveal that both ChatGPT usage and work motivation have positive and significant effects on teaching readiness, with work motivation emerging as the strongest predictor. Moreover, the simultaneous impact of both variables explains a substantial proportion of variance in teaching readiness, indicating a synergistic relationship between technological utilization and psychological factors. The study concludes that effective AI integration in education must be accompanied by strong work motivation to enhance teachers’ preparedness. Ultimately, this research invites readers to reflect on how technology and human motivation together shape sustainable teaching readiness in the AI-supported educational landscape.